Effectiveness of quadratus lumborum block and erector spinae plane block for post-operative analgesia in open urological procedures - Arsha P Santhosh; Ravi Prakash; Rajiv Dwivedi (Asian Journal of Medical Sciences)
Background: Open surgeries are associated with significant morbidities postoperatively such as pain and restricted ambulation causing delayed recovery. Among the various regional anesthesia techniques quadratus lumborum block (QLB) and erector spinae plane block (ESPB) are found to be effective alternatives.